2016
DOI: 10.1080/17441692.2016.1217031
|View full text |Cite
|
Sign up to set email alerts
|

The effect of power outages on in-facility mortality in healthcare facilities: Evidence from Ghana

Abstract: The World Bank estimates that at least 25 countries in the Sub-Saharan region of Africa experience chronic power outages. However, the implications of power shortages are often discussed within the context of industrial and economic disruptions, with little attention given to the health impact. Using a nationally representative data of healthcare facilities from the 2012 Ghana Access, Bottlenecks, Cost and Equity (ABCE) Health Facility Survey, this study aims to assess the impact of power outages on in-healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…The authors observed a statistically significant, positive association, with the risk of in-facility mortality increasing by approximately 43% for every day with a power outage of 2 or more hours (Apenteng et al, 2018). Interestingly, the risk of in-facility mortality was lower in rural health facilities compared to urban with the same power outage frequency, potentially because health care workers in rural facilities are more accustomed to operating without electricity (Apenteng et al, 2018).…”
Section: Health Effects Of Electricity Reliabilitymentioning
confidence: 96%
See 4 more Smart Citations
“…The authors observed a statistically significant, positive association, with the risk of in-facility mortality increasing by approximately 43% for every day with a power outage of 2 or more hours (Apenteng et al, 2018). Interestingly, the risk of in-facility mortality was lower in rural health facilities compared to urban with the same power outage frequency, potentially because health care workers in rural facilities are more accustomed to operating without electricity (Apenteng et al, 2018).…”
Section: Health Effects Of Electricity Reliabilitymentioning
confidence: 96%
“…Mortality. Just one study examined the effect of poor electricity reliability on mortality, with Apenteng, Opoku, Ansong, Akowuah, and Afriyie-Gyawu (2018) using a longitudinal study design to assess the association between the frequency of power outages in health facilities in Ghana and the total number of in-facility deaths (Apenteng et al, 2018). The authors observed a statistically significant, positive association, with the risk of in-facility mortality increasing by approximately 43% for every day with a power outage of 2 or more hours (Apenteng et al, 2018).…”
Section: Health Effects Of Electricity Reliabilitymentioning
confidence: 99%
See 3 more Smart Citations